Acute-On-Chronic Liver Failure Defined by Asian Pacific Association for the Study of the Liver Should Include Decompensated Cirrhosis - Xu, Manman; Kong, Ming; Yu, Pengfei; Cao, Yingying; Liu, Fang; Zhu, Bing; Zhang, Yizhi; Lu, Wang; Zou, Huaibin; You, Shaoli; Xin, Shaojie; Duan, Zhongping; et al. (Frontiers in Medicine, 2021)
Background and Aims: Acute-on-chronic liver failure (ACLF) is an acute deterioration of chronic liver disease with high short-term mortality. The inclusion or exclusion of previously decompensated cirrhosis (DC) in the diagnostic criteria of ACLF defined by Asian Pacific Association for the Study of the Liver (APASL-ACLF) has not been conclusive. We aimed to evaluate the prognostic impact of decompensated cirrhosis in ACLF. Methods: We retrospectively collected a cohort of patients with a diagnosis of APASL-ACLF (with or without DC) hospitalized from 2012 to 2020 at 3 liver units in tertiary hospitals. Baseline characteristics and survival data at 28, 90, 180, 360, 540, and 720 days were collected. Results: Of the patients assessed using APASL-ACLF criteria without the diagnostic indicator of chronic liver disease, 689 patients were diagnosed with ACLF, of whom 435 had no decompensated cirrhosis (non-DC-ACLF) and 254 had previously decompensated cirrhosis(DC-ACLF).The 28-, 90-, 180-, 360-, 540-, and 720-day mortality were 24.8%, 42.9%, 48.7%, 57.3%, 63.4%, and 68.1%, respectively, in DC-ACLF patients, which were significantly higher than in non-DC-ACLF patients (P<0.05). DC was independently associated with long-term (180/360/540/720 days) mortality but not short-term (28/90 days) mortality in patients with ACLF. Age, total bilirubin, international normalized ratio and hepatic encephalopathy were independent risk factors for short- and long-term mortality risk in ACLF patients (P < 0.05). Conclusions: Patients with DC-ACLF have a higher mortality rate, especially long-term mortality, compared to non-DC-ACLF patients, therefore, DC should be included in the diagnostic criteria of APASL-ACLF and treated according to the ACLF management process.